What makes a great clinical trial in physiotherapy?. (3rd October 2022) - Zadro, Joshua R.; Amorim, Anita B.; Ferreira, Giovanni; Hu, Xiaocong; Becerra, Rosa E.; Reza, Broti S.; Khan, Samar; Moseley, Anne M.
ABSTRACT: Objective: To identify common characteristics of landmark physiotherapy clinical trials. Methods: The Physiotherapy Evidence Database (PEDro) top five trials were compared to 91 physiotherapy trials published in top medical journals and 99 trials randomly selected from PEDro on the following characteristics: PEDro score, sample size, number of trial sites, use of prospective registration, positive or negative trial, citations, citations in guidelines, Altmetric score, impact factor, publications and citations of first and last author, and PEDro codes (sub-discipline, topic, problem, therapy, and body part). Trials were published from 2014 to 2019. One-way independent ANOVA and Chi–squared test evaluated between-group differences. Results: Compared to a random sample of physiotherapy trials, the PEDro top five trials and trials in top medical journals have higher PEDro scores, larger sample sizes, more study sites, more citations (including in guidelines), higher Altmetric scores, more likely to be prospectively registered, less likely to be positive trials, and have first and last authors with more citations and publications. The problem was the only PEDro code was distributed differently across the trial groups. Conclusion: The PEDro top five trials and physiotherapy trials published in the top medical journals have characteristics that may inform the design, conduct, and reporting of future physiotherapy trials.